Garbage Can Model at Covid 19 Countermeasures Policy in Banten - Gilang Ramadhan (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2021)
The Garbage Can Model is a public policy model that is taken by the government when an urgent event occurs which requires a fast and populist policy. Covid 19 is a deadly virus that spreads very quickly and is transmitted through human intermediaries, data released by the Covid 19 Response Acceleration Task Force on April 24, 2020, at least 8,211 people tested positive for this virus, and those who died reached 689 people and recovered 1,002 people. As for cases in the world, 2,626,321 people have tested positive, who died reaching 181,938 people covering 213 countries / regions (WHO Data Last update: 24 April 2020, 07:00 GMT + 7). In tackling the spread of this virus, the state as the policy holder has a stake in protecting the safety of its citizens. However, there are several cases where the policy dynamics are very intense, resulting in policy actors not being able to fully utilize their rational capacities. This study focuses on a number of government policies in the response to covid 19 which especially occurs in Banten. This study uses a qualitative methodology with a descriptive approach to better describe how it is possible to understand all actors involved in the covid 19 prevention policy in Banten. Finding of this research garbage can model can’t runs well, the four element of garbage can such alternative choice (policy window), problems, solutions, and participants can’t go hand in hand. The very large role of the participants limits the roles of other elements that actually play an important role in shaping the garbage can.